Complete sequence of three plasmids from Bacillus thuringiensis INTA-FR7-4 environmental isolate and comparison with related plasmids from the Bacillus cereus group - Amadio, Ariel Fernando (2009)
Bacillus thuringiensis is an insect pathogen used worldwide as a bioinsecticide. It belongs tothe Bacillus cereus sensu lato group as well as Bacillus anthracis and B. cereus. Plasmids fromthis group of organisms have been implicated in pathogenicity as they carry the genesresponsible for different types of diseases that affect mammals and insects. Some plasmids,like pAW63 and pBT9727, encode a functional conjugation machinery allowing them to betransferred to a recipient cell. They also share extensive homology with the non-functionalconjugation apparatus of pXO2 from B. anthracis. In this study we report the completesequence of three plasmids from an environmental B. thuringiensis isolate from Argentina,obtained by a shotgun sequencing method. We obtained the complete nucleotide sequenceof plasmids pFR12 (12 095 bp), pFR12.5 (12 459 bp) and pFR55 (55 712 bp) from B. thuringiensisINTA-FR7-4. pFR12 and pFR12.5 were classified as cryptic as they do not code forany obvious functions besides replication and mobilization. Both small plasmids were classifiedas RCR plasmids due to similarities with the replicases they encode. Plasmid pFR55showed a structural organization similar to that observed for plasmids pAW63, pBT9727and pXO2. pFR55 also shares a tra region with these plasmids, containing genes relatedto T4SS and conjugation. A comparison between pFR55 and conjugative plasmids led tothe postulation that pFR55 is a conjugative plasmid. Genes related to replication functionsin pFR55 are different to those described for plasmids with known complete sequences.pFR55 is the first completely sequenced plasmid with a replication machinery related tothat of ori44. The analysis of the complete sequence of plasmids from an environmentalisolate of B. thuringiensis permitted the identification of a near complete conjugation apparatusin pFR55, resembling those of plasmids pAW63, pBT9727 and pXO2. The availabilityof this sequence is a step forward in the study of the molecular basis of the conjugative processin Gram positive bacteria, particularly due to the similarity with known conjugationsystems. It is also a contribution to the expansion of the non-pathogenic B. cereus plasmidgene pool.